Classroom Transaction to Deal with Fear and Phobia in Developing Basic Mathematical Concepts - Dahiya, M.S. (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
Pedagogy means "The Art of teaching" Pedagogy of Mathematics is the Art/skill of teaching Mathematics. This paper highlights the basic difference between Telling and Teaching of Mathematics. Telling means making oral statement regarding some mathematical concepts and facts and expected from the learner to remember these, whereas teaching includes organization of activities and demonstration with illustrations to make the learners understand the concepts and facts. Effective pedagogy will help learners in developing their confidence and to overcome from fear and phobia for learning mathematical concepts/facts.  Mathematics Pedagogy involves certain important steps like to diagnose the hard spots of learning basic mathematical concepts and to devise remedial measures.  Mathematics Pedagogy is similar to clinical Pedagogy. As the doctor first diagnoses the problem and then takes decision to adopt remedial measures for the treatment of the diseases.  In Mathematics also at the first stage Diagnostic Evaluation is done to identify the hard spots of learning and then the remedial Effective pedagogy focuses on developing higher order thinking and makes the best use of the participation of the learner. Interactions, among teachers and students in a learning environment, help in developing sustainable learning among the learners. The use of various pedagogical skills helps in removing the fear and phobia among the learner in learning mathematical concepts.  Telling v/s Teaching methodology for facilitating Mathematics learning has been tried by the author in upper primary and secondary level classes. For Example: A fraction is a part of a unit or of a group of similar things.  This is one way of explaining the meaning of fraction.  Demonstrating the concept of a fraction involving the learner using concrete material is the best pedagogical skill for this particular concept. The paper focuses on the use of best Mathematical Pedagogy to be used in the class room transaction with the involvement of learners. Use of Hands on Activities with the involvement of learner followed by the assessment for learning and re-learning.